Clinical presentation of myocarditis in pediatric: the role of cardiac magnetic resonance in diagnosis (Medical Journal of Indonesia, 2014)
Myocarditis is an inflammatory disease of myocard with varied onset and clinical presentation which lead to diagnosis difficulties. These difficulties often cause incoming patients with acute condition are not diagnosed as acute myocarditis that subsequently may lead to improper therapy. This circumstance will probably cause more severe myocardial injury and even sudden death. On another circumstance, patients may also come late in conditions of dilated cardiomyopathy (DCM) or aritmogenik cardiomyopathy (ARVD) due to complexities of myocarditis early detection. Therefore, myocarditis diagnosis is extremely important. This case shows how CMR is important and highly accurate in diagnosing myocarditis through a case whereby a boy had complaints of chest pain and his CMR examination showed normal cardiac morphology with normal function of right and left ventricular, but with myocardial edema and tissue fibrosis, which confirmed the diagnosis of myocarditis according to the Lake Louise Consensus criteria. CMR is an important and high accuracy non-invasive diagnostic tool in myocarditis diagnosis.